(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the critical relationship between medical prescriptions and pharmacological drug administration. It explores the regulatory frameworks governing prescription practices, the importance of dosage accuracy, and the potential risks associated with drug misuse or self-medication. Furthermore, the study analyzes the impact of digital healthcare systems on prescription efficiency and patient safety. By evaluating the pharmacological properties and therapeutic effects of various drug classes, the research emphasizes the necessity of professional medical oversight in ensuring public health and minimizing adverse drug reactions.